The impact of project management skills, IT integration, supply chain coordination, process innovation, and communication language on organizational performance in educational institutions - Mohammed Al Matalka; Mohammad Alzoubi; Wadha Al Zouair; Mohamed Kamel AlDowaikat; Shadi Said Alkhazaleh; Ahmad Ibrahim Khalid Matalqeh (Journal of Project Management)
This study investigates the impact of project management capabilities on organizational performance, with a particular focus on the mediating roles of supply coordination, information technology integration, and process innovation. Data was collected from 85 suppliers providing goods and services to educational institutions in Irbid, Jordan, through questionnaires distributed from January 2025. The research adopts a causal quantitative approach, SEM-PLS to analyze the relationships between the variables. The findings reveal that project management capabilities positively influence supply coordination, information technology integration, and process innovation. Moreover, information technology integration and supply coordination significantly enhance organizational performance. This study contributes to a deeper understanding of how project management practices, supported by effective technology integration and strong supply chain coordination, can lead to improvements in organizational performance, especially within educational settings. The results underscore the importance of aligning project management capabilities with technological and collaborative strategies to promote innovation and efficiency.